The effect of a mindfulness-based cognitive therapy program on the spiritual health of mothers of infants admitted to the neonatal intensive care unit - Arasteh, Naeime; Moghimian Shahrbabaki, Reihane; Nematollahi, Monirsadat; Ahmadi, Atefe; Bagherian, Behnaz (Frontiers in Psychology, 2025)
Introduction The birth and admission of a premature infant to the NICU is often an unexpected experience and a mental and spiritual challenge for families. Spiritual health is an influential factor affecting how a mother faces and endures a stressful situation. Improving the mother's spiritual health requires cognitive therapy approaches, including mindfulness techniques. Nurses can help mothers of infants admitted to the NICU to go through the hospitalization period more peacefully by using mindfulness techniques. To this end, the present study sought to investigate the effect of a mindfulness-based cognitive therapy (MBCT) program on spiritual health in mothers of infants admitted to the NICU. Methods This quasi-experimental study was conducted using a pre-test-post-test design in two intervention and control groups. The participants were 50 mothers of infants admitted to the NICU of Afzalipur Hospital, Kerman, who were selected via convenience sampling and randomly divided into two control and intervention groups (25 mothers in each group). The intervention involved providing counseling using a short-term mindfulness-based cognitive therapy program carried out in four 2-h sessions for the participants in the intervention group. The participants in the control group received routine NICU care. The participants in both groups completed a demographic information questionnaire and the Spiritual WellBeing Scale (SWBS) before and after the intervention. The collected data were analyzed with SPSS-25 software. Results The data showed no statistically significant difference between the two groups in terms of demographic characteristics (P > 0.05). Moreover, the mean score of spiritual health in the intervention group was 92.80 ± 12.14 and that of the control group was 92.16 ± 16.35 before the intervention. The mean score of spiritual health in the intervention group was 104.04 ± 6.60 and that of the control group was 92.56 ± 16.35 after the intervention. The results of the paired samples t-test revealed a statistically significant difference in the mean scores of spiritual health and its dimensions before and after the intervention in the intervention group (P < 0.001). Discussion The findings from the present study indicated that mindfulness-based cognitive therapy intervention was effective in improving the spiritual health of mothers with infants admitted to the NICU. NICU nurses can use mindfulness-based cognitive therapy as a practical intervention to improve the spiritual health of mothers of premature infants and promote the sense of meaningfulness and meaning of life in these mothers.